Using E-Module in Guidance Lessons to Enhance Multicultural Self-Efficacy of Islamic and Public High School Students - Yosef Yosef; Fadhlina Rozzaqyah; Rahmi Rahmi; Alika S Marwah; Vin Vilala (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2023)
The implication of multiculturally Islamic and public high schools for guidance and counseling was how to help students enhance multicultural self-efficacy using self-learning electronic based-materials. The current study examined the effect of using an e-module of guidance lessons on students' multicultural self-efficacy. It constituted 10th graders of an Islamic High School (IHS) and a Public High School (PHS) as its samples. A Multicultural Self-Efficacy Scale (MSES) was employed to measure students' multicultural self-efficacy before and after completing the self-instruction of the guidance lesson comprising five units of an e-module. The study analyzed the data sets employing a paired sample t-test, independent t-tests, and N-gain techniques to test the hypotheses. The results revealed the significant effect of using the e-module on the multicultural self-efficacy of Islamic and public high school students, no significant differences between the multicultural self-efficacy of IHS and PBS students, and the value of using the e-module was at a moderate level for both groups. In conclusion, using the e-module could provide a functional account of guidance lessons to increase multicultural self-efficacy among students of IHS and PHS.